The Coast Salish Knitters and the Cowichan Sweater: An Event of National Historic Significance - Stopp, Marianne (Material Culture Review, 2012)
Abstract Long before the arrival of Europeans, the Coast Salish First Nations of southwestern Vancouver Island turned mountain goat wool, dog hair and plant fibres into woven textiles of great value among the peoples of the Pacific Northwest. Around 1860, Coast Salish women in the Cowichan Valley were introduced to European two-needle and multiple-needle knitting and began to produce what came to be known as the Cowichan sweater. Preparation combined ancient fibre processing and spinning techniques with European knitting to produce a high-quality, iconic garment. Profit margins for the knitters were minimal, but knitting provided an economic foothold in a new and challenging market-based economy. In 2011, the Government of Canada designated the Coast Salish Knitters and the Cowichan Sweater as an event of national historic significance on the advice of the Historic Sites and Monuments Board of Canada.